Deontic authority in intervention discourse: Insights from bystander intervention. (October 2019) - Ran, Yongping; Huang, Xu
Our study offers a linguistic–pragmatic examination of instances of bystander intervention, a social action that takes place when a bystander or a group of bystanders intervenes when a wrongdoer abuses a victim or behaves outside socially acceptable norms. We approach this social phenomenon by analyzing data drawn from a database of 11 video-recordings that all involve naturally occurring interactions in public settings in China. The notion of intervention discourse is tentatively introduced in this study to distinguish it from those used to achieve other communicative purposes and to disclose some recurrent patterns of language use in bystander intervention. The data analysis summarizes six categories of intervention discourse along the continuum of strong to weak intervention: terminating, consequence-stating, advising, judging, appealing and stance-taking. Our study demonstrates that the skillful exercise of deontic authority embodied in intervention discourse might have a tangible influence on the outcome of the intervention.